Characteristics of scientific knowledge progress in the information age: methodological analysis - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article investigates the characteristics of the process of scientific study in the Information Age.